Immunization care movement efforts towards 100% achievements in UCI Village, Sabu Liae District, Sabu Raijua Districts, 2018 - 2020 - Lino, Marianus; Ha'e, Lisias; Radja, Isak (BKM Public Health and Community Medicine, 2021)
The dynamics of health and illness are two sides of the controversy that never stop and end forever. The high frequency of incidence of infectious and degenerative diseases in society is currently a (double burden) that has not been resolved, especially the spread of infectious diseases that do not recognize age and administrative boundaries so that it requires various countermeasures periodically, integrated and across sectors. In Law No. 36 of 2009 concerning Health, Immunization is one of the efforts to prevent infectious diseases and is a priority activity of the Ministry of Health in order to achieve SDGs, especially to reduce mortality in children. This scientific work aims to encourage community participation as a driving force towards the movement for healthy living (GERMAS) communities and to increase the independence and active participation of all Natural Leaders and village stakeholders in Sabu Liae District in the health sector, especially in the immunization program. The research design in scientific papers is analytic observation. The results that the UCI achievement at Eilogo Health Center was still low where in 2019 (90%), 2020 (70.50%), so that in order to answer the above problems, strategic programs and innovations carried out are community empowerment using the IMMUNIZATION CARE FORUM (FPI) movement approach, considering Eilogo Public Health Center as one of the spearheads of integrated and foremost health services in Sabu Raijua Regency has the responsibility of implementing health services. Immunization services are routinely carried out every month at 40 Immunization points spread across 40 posyandu throughout Sabu Liae District. To support innovation work on community empowerment through the Immunization Care Forum, it is hoped that the support of the Government will become the pioneer UKBM for the formation of new FPI in all sub-districts throughout Sabu Raijua Regency.